2023
DOI: 10.1007/s10441-023-09460-y
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Model of COVID-19 Pandemic with Double Dose Vaccination

Abstract: This paper is concerned with the formulation and analysis of an epidemic model of COVID-19 governed by an eight-dimensional system of ordinary differential equations, by taking into account the first dose and the second dose of vaccinated individuals in the population. The developed model is analyzed and the threshold quantity known as the control reproduction number is obtained. We investigate the equilibrium stability of the system, and the COVID-free equilibrium is said to be locally asymptotica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…In addition to vaccine efficacy, vaccination policy must also account for factors such as vaccination program design and optimal dosing strategies. Recent research has underscored the value of modeling and simulation studies for exploring the potential impact of double doses [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to vaccine efficacy, vaccination policy must also account for factors such as vaccination program design and optimal dosing strategies. Recent research has underscored the value of modeling and simulation studies for exploring the potential impact of double doses [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The studies of Paul et al [ 37 ] and Peter et al [ 38 ] have also shown that a full vaccination program can significantly reduce cases and impact disease eradication. Public health professionals can use this information to effectively control COVID-19 outbreaks in Bangladesh [ 37 ] and Malaysia [ 38 ]. Overall, mass vaccination exercises are crucial in achieving herd immunity and preventing further outbreaks of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Global sensitivity analysis will be carried out, using Latin Hypercube Sampling (LHS) and Partial Rank Correlation Coefficients (PRCCs) [94][95][96], on the WBE model {(2.2)(2.3)} to determine the parameters that have the most influence on a chosen response function. Various SARS-CoV-2 modeling studies have chosen the reproduction number of the models (a measure of the average number of new cases generated by a typical infectious individual over the duration of their infectiousness) as the response function [53,65,97,98]. In this study, we will use the cumulative viral load in wastewater (W ) as the response function.…”
Section: Global Sensitivity Analysismentioning
confidence: 99%
“…To study the dynamics of COVID-19, mathematical models and optimal controls are required to predict and emphasize disease transmission, recovery, death, and other significant parameters individually for disparate countries, that is, the reported range of high too low for specific regions of the COVID-19 cases. Several modeling approaches have been used in numerous research studies [2][3][4][5][6][7]. Kamrujjaman et al (2022) [2] proposed a deterministic mathematical model for the COVID-19 outbreak and validated the model using real data from Italy from 15th Feb 2020 to 14th July 2020.…”
Section: Introductionmentioning
confidence: 99%